A dislocation density based constitutive model for as-cast Al-Si alloys: Effect of temperature and microstructure. (February 2017) - Zamani, Mohammadreza; Dini, Hoda; Svoboda, Ales; Lindgren, Lars-Erik; Seifeddine, Salem; Andersson, Nils-Eric; Jarfors, Anders E.W.
Abstract: The flow stress of an as-cast Al-Si based alloy was modeled using a dislocation density based model. The developed dislocation density-based constitutive model describes the flow curve of the alloy with various microstructures at quite wide temperature range. Experimental data in the form of stress-strain curves for different strain rates ranging from 10 −4 to 10 −1 s −1 and temperatures ranging from ambient temperature up to 400 °C were used for model calibration. In order to model precisely the hardening and recovery process at elevated temperature, the interaction between vacancies and dissolved Si was included. The calibrated temperature dependent parameters for different microstructure were correlated to the metallurgical event of the material and validated. For the first time, a dislocation density based model was successfully developed for Al-Si cast alloys. The findings of this work expanded the knowledge on short strain tensile deformation behaviour of these type of alloys at different temperature, which is a critical element for conducting a reliable microstructural FE-simulation. Highlights: A physic-based dislocation density model was developed for an as-cast Al-Si alloy. The model describes the flow stress of the alloy from room temperature up to 400 °C. The include the effect Si solute and vacancies interaction on hardening and recovery. Eutectic Si and intermetallics have diminished role on hardening process at small strain. Si solute atoms in α-Al matrix increase the equilibrium vacancy concentration.